2008
DOI: 10.1038/sj.ijo.0803791
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evidence of altered cardiac autonomic function in overweight but not underweight subjects

Abstract: Background:Little is known about the altered cardiac autonomic function (CAF) across different levels of body mass index (BMI), including underweight, normal weight, overweight and obesity. This study provides a thorough analysis to clarify the CAF change in subjects with underweight, overweight and obesity. Methods: According to the World Health Organization (WHO) Asia-Pacific BMI cutoffs, a total of 1437 participants were classified as underweight (n ¼ 74), normal weight (n ¼ 588), overweight (n ¼ 313), obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
1
12
1
1
Order By: Relevance
“…In our study, females had a significantly higher HR and RSA, but lower SDNN compared with males, which is in accordance with earlier findings (50 -52). Although several papers have been published on HRV and obesity, few studies have addressed the relationship between HRV and continuous BMI, and findings have been inconsistent (50,(53)(54)(55). In line with Kageyama et al (55) and Britton et al (53), we found that an increase in BMI was significantly associated with an increase in HR and a decrease in SDNN, but the effect of BMI on RSA was not significant.…”
Section: Licht Et Alsupporting
confidence: 77%
“…In our study, females had a significantly higher HR and RSA, but lower SDNN compared with males, which is in accordance with earlier findings (50 -52). Although several papers have been published on HRV and obesity, few studies have addressed the relationship between HRV and continuous BMI, and findings have been inconsistent (50,(53)(54)(55). In line with Kageyama et al (55) and Britton et al (53), we found that an increase in BMI was significantly associated with an increase in HR and a decrease in SDNN, but the effect of BMI on RSA was not significant.…”
Section: Licht Et Alsupporting
confidence: 77%
“…In his epidemiological survey, Wu et al . () disclosed no significant differences in any index of HRV between NW and UW subjects, thus indicating that the sympathovagal modulation of HR in UW subjects did not seem apparently reduced. Krishna et al .…”
Section: Discussionmentioning
confidence: 83%
“…The relationship between HRV and BMI was investigated by Wu et al . () who found HRV reduction in obese subjects, compared to normal weight (NW) subjects, whereas no differences were evidenced between UW and NW subjects. However, these authors did not address any comparison between UW and obese subjects.…”
Section: Introductionmentioning
confidence: 93%
“…Previous findings have revealed that gender, age, body mass index (BMI), physical activity, and alcohol use are among the factors significantly affecting the autonomic control of heart rate (Antelmi et al, 2004;Chen et al, 2015;Kuo et al, 1999;Rosenwinkel et al, 2001;Wu et al, 2008). These factors were thus selected as control variables.…”
Section: Control Variablesmentioning
confidence: 99%